Compressed air energy storage in integrated energy systems: A review. (October 2022) - Bazdar, Elaheh; Sameti, Mohammad; Nasiri, Fuzhan; Haghighat, Fariborz
Abstract: The intermittency nature of renewables adds several uncertainties to energy systems and consequently causes supply and demand mismatch. Therefore, incorporating the energy storage system (ESS) into the energy systems could be a great strategy to manage these issues and provide the energy systems with technical, economic, and environmental benefits. Among all energy storage systems, the compressed air energy storage (CAES) as mechanical energy storage has shown its unique eligibility in terms of clean storage medium, scalability, high lifetime, long discharge time, low self-discharge, high durability, and relatively low capital cost per unit of stored energy. In contrast, low roundtrip efficiency (RTE), low depth of discharge, and high response time are considered its main drawbacks. This paper presents a comprehensive review of technological developments in CAES systems, including its design criteria and emerging application potentials. Furthermore, a detailed review of the most recent research progress on CAES technology and its challenges is presented from the point of view of the different integration potential of CAES, optimal designing, and scheduling with the role of CAES towards micro-grid, distribution energy network, and energy market environment. Finally, the limitations and future perspectives of CAES are described and summarized. This paper presents a comprehensive reference for integrating and planning different types of CAES in energy systems for various applications. Highlights: A review of the CAES practical applications and characteristics is carried out. A comprehensive classification and comparison of various CAES are given. The concept of CAES integration with energy conversion systems is introduced. Different approaches for sizing the CAES components are presented. CAES's optimal scheduling is discussed from the energy market, distribution network, and microgrid perspective.